Feminicídio: um estudo sobre a atuação policial em uma delegacia de homicídios e proteção às mulheres - Carneiro, Igor de Oliveira (2023)
Introduction: According to the United Nations, violence against women is an act that is directly related to gender, from which physical, moral, sexual and psychological aggressions can be derived, which restrict and threaten the victims in what concerns their freedom in the various social spheres.The state of Espírito Santo was a pioneer in creating the Police Station for Homicide and Protection of Women in September 2010. This initiative was implemented by the Civil Police to investigate crimes against life committed against women in the municipalities of Vitória, Vila Velha, Serra, Cariacica and Viana. In Brazil, Law nº 13104/2015, also known as the Feminicide Law, came into force on March 10, 2015, as a response to increasing violence against women. This law establishes that femicide is considered an aggravating factor for the crime of homicide, framing it as a heinous crime. This means that, if the crime is motivated by female gender issues, it is configured as femicide, highlighting the importance of identifying aspects of gender violence. With the enactment of the Femicide Law, this police unit began to look for new elements that could prove the occurrence of these crimes, taking into account the aspects established by the law. The problem consists in identifying the existence of gender violence, concerning contempt or discrimination, suffered by women who are victims of feminicides in the municipalities mentioned in the scope of the police station, given the immediacy and urgency of a police approach, given the complexity of the theme. Therefore, the main objective is to propose alternatives to understand the power relations and gender construction of the crimes under investigation, in order to contextualize this problem in the investigation of crimes against women. The theoretical contribution focused on the concepts brought by Law nº 13104/2015 and relevant legislation, correlating with intersectional debates that permeate Yuval-Davis and Anthias to Crenshaw and gender violence in Scott and Saffioti. As for methods and procedures, a mixed approach was carried out, through descriptive quantitative analysis of the victims' data, extracted from police inquiries completed by the police station, referring to race, age, social class and relationship with the aggressors, and documentary-descriptive research about of the characterization of gender violence, supported by bibliographical research. The result showed that the majority of victims of completed femicide investigated in the police unit are black and that after the enactment of law nº 13104/2015, a lower percentage of black victims and a higher percentage of nonblack victims were identified in relation to crimes of passion. This fact was also verified during the Covid-19 pandemic, in which the number of consummated feminicides of black women decreased and non-black women increased, which shows that gender violence covers a wide range of factors that are not always readily identified. throughout feminicide investigations, it is crucial that the agents responsible for the investigation have resources and in-depth knowledge on the subject, in order to understand the complexities and elements involved in these cases. Based on this information, as a technical-technological product, a booklet was developed with guidelines for managers responsible for conducting femicide investigations, in order to enable a more comprehensive understanding of the causes of this specific form of violence, allowing for more effective action in the field. combat this type of crime.